2012
DOI: 10.1177/0306624x12469602
|View full text |Cite
|
Sign up to set email alerts
|

Prisoners’ Assessments of Mental Health Problems Among Their Children

Abstract: High rates of imprisonment among American men and women have motivated recent research on the well-being of children of incarcerated parents. Despite advances in the literature, little is known regarding the mental health status of children who experience maternal relative to paternal incarceration. Accordingly, we examine whether there are differences in mental health needs among children of incarcerated parents. Specifically, we assess whether incarcerated mothers are more likely than incarcerated fathers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 52 publications
0
23
0
1
Order By: Relevance
“…The higher use of mental health counseling among individuals with a history of FI likely reflects a greater mental health burden in this population but does not necessarily indicate adequate mental health treatment. 16,31 Additionally, young adults with MI are more likely to use the ED as their usual source of health care. These young adults may seek care after their health problems have worsened, propagating existing health disparities experienced by individuals with exposure to MI.…”
Section: Discussionmentioning
confidence: 99%
“…The higher use of mental health counseling among individuals with a history of FI likely reflects a greater mental health burden in this population but does not necessarily indicate adequate mental health treatment. 16,31 Additionally, young adults with MI are more likely to use the ED as their usual source of health care. These young adults may seek care after their health problems have worsened, propagating existing health disparities experienced by individuals with exposure to MI.…”
Section: Discussionmentioning
confidence: 99%
“…The painful journey and bureaucratic battles that many of the women we interviewed undertook to reestablish their motherhood role and the importance of this role in solidifying their prosocial identities underscore the importance of correctional programming that fosters familial relationships. Many others have called for gender-responsive programming (for a review, see Van Voorhis, 2012) that includes policies aimed at reducing parental stress and increasing the likelihood of family reunification (Arditti & Few, 2006;Burgess & Flynn, 2013;Celinska & Siegel, 2010;Hoffmann, Byrd, & Kightlinger, 2010;Tasca, Turanovic, White, & Rodriguez, 2014). Reentry must begin well before release and should consider the need for inexpensive mediation and reconciliation forums for inmates and their family members.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the considerable groundwork that has been laid to identify correlates of emotional and behavioral problems common among children of incarcerated mothers (e.g., Arditti, 2012;Phillips et al, 2002;Tasca et al, 2014), the factors associated with their mental health service use remained unclear. Accordingly, the purpose of this study was to examine the various child, mother, and caregiver characteristics associated with whether children receive mental health treatment during maternal incarceration.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown anxiety, depression, and other internalizing problems to be common among children of incarcerated mothers (Geller, Garfinkel, Cooper, & Mincy, 2009; Kampfner, 1995; Phillips, Burns, Wagner, Kramer, & Robbins, 2002). And while the evidence is conflicting as to whether these problems stem directly from maternal imprisonment or from other preexisting life difficulties (e.g., early childhood trauma or prenatal exposure to drugs and alcohol; Johnston, 2006; Murray, Farrington, & Sekol, 2012; Wildeman & Turney, 2014), there is consensus that children of incarcerated mothers face a great deal of mental health concerns (Dallaire, 2007; Dallaire & Wilson, 2010; Tasca, Turanovic, White, & Rodriguez, 2014). This is problematic considering that in U.S. state prisons alone, there are approximately 65,600 incarcerated mothers who are parents of more than 147,400 minor children (Glaze & Maruschak, 2008).…”
mentioning
confidence: 99%